2016
DOI: 10.3389/fnagi.2015.00254
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Mindfulness Meditation on Brain's White Matter Microstructure and its Aging

Abstract: Although research on the effects of mindfulness meditation (MM) is increasing, still very little has been done to address its influence on the white matter (WM) of the brain. We hypothesized that the practice of MM might affect the WM microstructure adjacent to five brain regions of interest associated with mindfulness. Diffusion tensor imaging was employed on samples of meditators and non-meditators (n = 64) in order to investigate the effects of MM on group difference and aging. Tract-Based Spatial Statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
46
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 87 publications
(134 reference statements)
11
46
0
2
Order By: Relevance
“…This points to the AI's role in generating an interoceptive representation while affectively and empathically sharing another's embarrassing moments. Previous studies investigated structural changes in LTM practitioners and have suggested increased thickness [Lazar et al, ], increased cortical folding complexity [Luders et al, ], as well as increased connectivity of white matter within the insula cortex in meditators [Laneri et al, ]. These structural changes might constitute the architecture that underlies altered functioning of the AI cortex in LTM practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…This points to the AI's role in generating an interoceptive representation while affectively and empathically sharing another's embarrassing moments. Previous studies investigated structural changes in LTM practitioners and have suggested increased thickness [Lazar et al, ], increased cortical folding complexity [Luders et al, ], as well as increased connectivity of white matter within the insula cortex in meditators [Laneri et al, ]. These structural changes might constitute the architecture that underlies altered functioning of the AI cortex in LTM practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…Such cerebral responses appear to be associated with a greater ability to self-regulate emotions and control attention (Bing-Canar, Pizzuto, & Compton, 2016;Davidson et al, 2003). However, it is important to emphasize that the effects of meditation on brain activity can be moderated by a wide range of factors, such as the type of meditation, amount of sensory information provided, one's ability to focus, and previous experience with meditation (see e.g., Brewer et al, 2011;Laneri et al, 2016). It has also been identified that the practice of meditation can impact upon the connectivity between frontal and temporo-parietal regions of the brain (Berkovich-Ohana, Glicksohn, & Goldstein, 2013;Taren et al, 2017).…”
Section: Psychophysiological Mechanismsmentioning
confidence: 99%
“…For a complete list of those studies as well as for details on data processing and analysis, the reader is referred to the original publication . In close correspondence with the aforementioned findings in this field of research, the authors of study III reported that “in all ROIs, apart from right insula and left ACC, the relationship between FA and age in non‐meditators demonstrates a natural FA decline in aging adults which could not be detected in meditators.” Unfortunately, group‐specific correlation coefficients are not provided, but the two scatterplots from study III show negative slopes in controls and either positive slopes (left insula) or less steep negative slopes (right thalamus) in meditators. Testing for group‐by‐age interactions, significant effects were observed within all ROIs, with a stronger age‐related decline in controls in white matter adjacent to the left and right thalamus, left and right amygdala, left and right hippocampus, left insula, and right ACC.…”
Section: New Research: 2013–2016mentioning
confidence: 73%
“…Following up on these previous findings, three novel cross-sectional imaging studies were conducted [17][18][19] examining whether meditators show less age-related decline of brain tissue. Study I 17 and study II 18 used MRI and were based on T1-weighted data obtained on a 1.5-Tesla scanner.…”
Section: New Research: 2013-2016mentioning
confidence: 99%
See 1 more Smart Citation